The Effect of Multifloral Honey Addition on The Physico-chemical and Sensory Evaluation of Marshmallow - Dedes Amertaningtyas; Shofiya Naifa Abidah; Zahra Diza Iqlima Didi Rosidi; Christbugi Welda Dellani; Aldyon Restu Azkarahman (Politeknik Pembangunan Pertanian Manokwari, 2026)
This study aimed to determine the effect of multifloral honey addition on the physicochemical and sensory evaluation of marshmallows. The research was conducted using a laboratory experiment with a Completely Randomized Design (CRD), if there are differences, the Duncan Multiple Range Test (DMRT) will be used. This study consisted of 4 treatments with 5 replications: without multifloral honey addition (M0), 15% multifloral honey concentration (M1), 30% multifloral honey concentration (M2), and 45% multifloral honey concentration (M3), calculated on a volume-to-volume basis (v/v) relative to the total gelatin used in the marshmallow formulation. The variables in this study included moisture content, water activity, chewiness, Lab* color, reducing sugar, ash content, antioxidant activity, and sensory evaluation. The result showed that multifloral honey addition had a highly significant effect (P<0.01) on moisture content, reducing sugar content, ash content, and antioxidant activity (IC50) of marshmallow, and had a significant effect (P<0.05) on the decrease of color sensory evaluation. Multifloral honey addition showed no significant effect (P>0.05) on water activity (Aw), chewiness (N), color Lab*, as well as sensory evaluation parameters (taste, aroma, texture, and overall acceptance). The average values of the moisture content of marshmallows ranged from 26.22–27.98%; Aw 0.703–0.733; chewiness 2.94–3.30 N; brightness level (L*) 92.81–93.65; redness (a*) -0.376 – (-0.568); yellowness (b*) 7.062– 8.016; reducing sugar content 8.99–20.95%; ash content 0.61–2.65%; antioxidant activity (IC50) 110.63–462.83µg/ml; sensory evaluation including taste 3.8–4.09; color 4.45–4.74; aroma 3.74–3.91; texture 3.54–3.91; and overall acceptance 3.83- 4.09. The formulation with 15% multifloral honey addition (M1) was indicated as the optimal treatment based on physicochemical and sensory evaluation.